1987
DOI: 10.1203/00006450-198705000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Lung Development in the Fetal Guinea Pig: Surfactant, Morphology, and Premature Viability

Abstract: ABSTRACT. Guinea pigs demonstrate "precocious" physical and functional development, with newborns displaying open eyes, hair, self-feeding, and temperature regulation. In addition, morphologic lung development is precocious in the guinea pig, with advanced alveolarization taking place in utero. To explore whether pulmonary surfactant development is also advanced, and at what stage prematurely delivered guinea pigs are capable of survival, we delivered fetal guinea pigs at 2-to 3-day intervals from day 49 of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(17 reference statements)
2
11
0
Order By: Relevance
“…However, the demonstrated decreased viability and significant physiologic immaturity of these preterm neonates suggest an earlier age equivalency. This is supported by previous studies in the guinea pig that have assessed lung development in the fetal guinea pig and suggest that pups born before 66 d GA show considerable lack of development, demonstrated by lung growth and development, and that guinea pig neonates born at <88% completed gestation cannot survive with non-invasive interventions (23). These findings are consistent with the significantly increased mortality of preterm guinea pig neonates observed in this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the demonstrated decreased viability and significant physiologic immaturity of these preterm neonates suggest an earlier age equivalency. This is supported by previous studies in the guinea pig that have assessed lung development in the fetal guinea pig and suggest that pups born before 66 d GA show considerable lack of development, demonstrated by lung growth and development, and that guinea pig neonates born at <88% completed gestation cannot survive with non-invasive interventions (23). These findings are consistent with the significantly increased mortality of preterm guinea pig neonates observed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have concluded that lung growth and development parallels the overall development of a species at birth (24). In a previous study of lung development, fetal guinea pigs at 61 d gestation had lung morphology indicative of the saccular stage of lung development, which is seen in the human neonate from approximately 24 wk of GA through to term (23). Viability and support levels in our neonatal guinea pigs suggest that they are more physiologically equivalent to a human infant born at approximately 29 wk completed gestation because approximately half of the infants born at this GA could be expected to survive with only our limited interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P4 has been shown to play a role in lung development (Beyer et al 2003;Trotter et al 2006Trotter et al , 2009 as well as in neurological development (Wagner 2008;Yawno et al 2014). These two organs manifest prolonged development in humans (and in guinea pig; Sosenko and Frank 1987), as evidenced by a majority of the defects from preterm birth being of neurological and pulmonary nature. It is tempting to speculate that the evolution of a metabolically costly brain (Clancy et al 2007), in particular given its growth spurt immediately following birth, may require lungs with exceptional capacity and long development.…”
Section: What May Drive Different Levels Of Progesterone Across Species?mentioning
confidence: 99%
“…During the next stage, the stage of alveolarization, the gasexchange surface increases dramatically due to the subdivision of the existing airspaces (sacculi) by the formation of new inter-airspace walls resulting in the appearance of the alveoli. Depending on species, alveolarization can be pre-or postnatal: in precocial animals like guinea pigs (36) and sheep (1), alveolar formation starts well before birth, and at term their lungs appear almost mature. In altricial species, alveolar formation is rather a postnatal event, like in rats (4,6), mice (2), and humans (46,47).…”
mentioning
confidence: 99%